A bibliometric analysis of 100 years of research on Himalayan cedar: research trends, gaps, and future implications - Kumar, Ashutosh; Pandey, Aseesh (Frontiers in Forests and Global Change, 2024)
Himalayan Cedar (Cedrus deodara), a member of the family Pinaceae is well-known for its ecological, economic, and cultural significance. It is native to the Western Himalayan region and listed as Least Concern in the IUCN list of threatened species. In the present study, a bibliometric analysis of more than a hundred years of research on C. deodara is carried out. Total 616 documents published from 1916-2024 were retrieved from the Scopus database and analysed using biblioshiny and VoS viewer. A comprehensive overview of publication trends, country-wise publications, bibliographic coupling, citation analysis, keyword analysis, and collaborative research networks are presented. The research findings revealed that publications have increased significantly in recent decades and primarily multidisciplinary. Forest ecology, pharmacology, phytochemistry, climate change, environmental science, and taxonomy were among the major thrust areas. However, recent studies are mostly focused on carbon stock, biomass, dendrochronology, and climate change. Out of the 362 publication sources, Bradford's law identified six journals as core sources for publication. Lotka' law revealed that only 8% of authors have published more than two documents on C. deodara. The present study provides a comprehensive evaluation and visualisation of C. deodara based bibliometric research carried out during the past 100 years. Further, the study provides collective information and a research framework for scholars, the general public, and decisionmakers by identifying research gaps and future research areas.